2008
DOI: 10.1007/s11355-008-0037-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agricultural land use on water chemistry of mire pools in the Ishikari Peatland, northern Japan

Abstract: Concomitant with farmland development in the Ishikari Peatland of northern Japan, deterioration of water chemistry has become increasingly evident at mire pools there. Using spatial analysis methods with a geographic information system and a statistical methodology, this study examined the effects of agricultural land use on the pool water chemistry. A water chemistry survey of several pools showed that nitrogen, phosphorus, and suspended-solid concentrations were remarkably higher than those in pools that had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…The second distinguished pair of ions, Na + and Ca 2+ , is very frequently interpreted in PCA of peat waters, together with other macro ions, as evidence of groundwater supply to peatlands (Blancher & McNicol 1987, Kizuka et al 2008, Stelmaszczyk et al 2009. Traces of penetration of KR by groundwaters are found in the depth distribution of PC2 values.…”
Section: Discussionmentioning
confidence: 99%
“…The second distinguished pair of ions, Na + and Ca 2+ , is very frequently interpreted in PCA of peat waters, together with other macro ions, as evidence of groundwater supply to peatlands (Blancher & McNicol 1987, Kizuka et al 2008, Stelmaszczyk et al 2009. Traces of penetration of KR by groundwaters are found in the depth distribution of PC2 values.…”
Section: Discussionmentioning
confidence: 99%
“…Marsh lakes occur in relatively downstream areas and have been in the same locations as far back as documented by existing records (aerial photographs and cartographic maps; oldest available 1917). Lakes are increasingly subjected to inputs of irrigation water drained from rice paddies, and deterioration of water quality has been reported (Kizuka et al, 2008). Natural lakes exist in relatively upstream areas.…”
Section: Study Sitementioning
confidence: 99%
“…However, most of the lakes have overland hydrological connections to the main channel via waterways with floodgates that are embedded in the dykes; these are shut only during large floods to prevent internal flooding. Lakes are increasingly subjected to inputs of irrigation water drained from rice paddies, and deterioration of water quality has been reported (Kizuka et al, 2008). We selected nine natural lakes, eight marsh lakes and five artificial lakes for the study; some lakes in the area were excluded from the survey because of obvious modifications of bottom bedforms (via past dredging) or water withdrawals during non-irrigation periods in winter.…”
Section: Study Sitementioning
confidence: 99%
“…Therefore, many small lakes in Japan do not meet waterquality standards. It has been reported that lakes surrounded by farming areas, in particular, are polluted (T. Kizuka, Yamada, Yazawa, & Chung, 2008).…”
Section: Introductionmentioning
confidence: 99%